2020
DOI: 10.3390/su12208620
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of CEOs’ Transformational Leadership on Sustainable Organizational Innovation in SMEs: A Three-Wave Mediating Role of Organizational Learning and Psychological Empowerment

Abstract: The sustainable organizational innovation is of paramount importance for enhancing productivity in firms and provides organizations with the strategic direction needed to allow them to perform at an international level. The leadership styles play a key role in their firms’ potential to consistently innovate. Using data from a time-lagged design with three waves, CEOs of Chinese small and medium-sized enterprises (SMEs) participated in the study. The findings reveal that psychological empowerment mediated the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 99 publications
4
29
0
Order By: Relevance
“…Transformational leadership at the school also encourages teachers to think with a global perspective. This study confirms the findings of Begum et al (2020) who examined the effect of transformational leadership on organizational learning in the context of small to medium enterprise CEOs in North China. The results of the study indicate a positive effect of the two variables.…”
Section: Transformational Leadership Has a Positive Effect On Olsupporting
confidence: 88%
See 1 more Smart Citation
“…Transformational leadership at the school also encourages teachers to think with a global perspective. This study confirms the findings of Begum et al (2020) who examined the effect of transformational leadership on organizational learning in the context of small to medium enterprise CEOs in North China. The results of the study indicate a positive effect of the two variables.…”
Section: Transformational Leadership Has a Positive Effect On Olsupporting
confidence: 88%
“…The results of the study indicate a positive effect of the two variables. Moreover, Begum et al (2020) found that transformational leadership is designed to promote knowledge transfer in organizational learning.…”
Section: Transformational Leadership Has a Positive Effect On Olmentioning
confidence: 99%
“…Due to the emerging technologies crucial for achieving success and building resilience in a time of adversity, organizations are required to evolve, progress, and innovate in response to contingency. Several leadership styles were discussed in recent literature as conducive to innovation and organizational sustainable economic development [86,105,130]. However, not all leadership styles are flexible enough to allow for agility when resources are scarce and responsiveness crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the skillful leader may empower followers by framing the danger as a challenge and opportunity for learning and self-development, thus ensuring that the stress is more productive than paralyzing. Employees should seemingly be instructed to engage in organizational learning and not to refrain from participation due to fear over the future uncertainty, as the imminent threat brings about a more uncertain future if the change does not take place [105]. The favorable attitude towards the change is stimulated for the main part by empowering leadership.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…These four cognitions reflect an active orientation to a work role, an orientation in which an individual wishes and feels able to shape role and context. Meaning in the context of empowerment indicates the value of the work goal or purpose, judged by concerning an individual's ideals and standards (Begum et al 2020).…”
Section: The Mediation Of Empowerment Between Entrepreneurial Leaders...mentioning
confidence: 99%